Origin of improved depth penetration in dual‐axis optical coherence tomography: a Monte Carlo study. Issue 6 (7th March 2019) - Zhao, Yang; Chu, Kengyeh K.; Jelly, Evan T.; Wax, Adam
Abstract : Recent studies have demonstrated that extended imaging depth can be achieved using dual‐axis optical coherence tomography (DA‐OCT). By illuminating and collecting at an oblique angle, multiple forward scattered photons from large probing depths are preferentially detected. However, the mechanism behind the enhancement of imaging depth needs further illumination. Here, the signal of a DA‐OCT system is studied using a Monte Carlo simulation. We modeled light transport in tissue and recorded the spatial and angular distribution of photons exiting the tissue surface. Results indicate that the spatial separation and offset angle created by the non‐telecentric scanning configuration promote the collection of more deeply propagating photons than conventional on‐axis OCT. Abstract : Extended imaging depth can be achieved using dual‐axis optical coherence tomography (DA‐OCT). In this study, the signal of a DA‐OCT system is studied using a Monte Carlo simulation. Results indicate that by illuminating and collecting at an oblique angle, the spatial separation and offset angle created by the non‐telecentric scanning configuration promote the collection of more deeply propagating photons than conventional on‐axis OCT.